Imaging approach for LAI determination of oil palm - Awal, Md. Awal; Wan Ishak, Wan Ismail; Endan, Johari; Harun, Mohd. Haniff (2005)
Leaf Area Index (LAI) describes a fundamental property of the plant canopy and its interaction with the atmosphere, such as radiation, photosynthesis, energy exchange and gas exchanges. LAI has often been used as a critical variable to simulate the growth and yield models, but it is difficult to measure directly for oil palm. The present conventional method used in determining LAI is laborious, difficult and time consuming. Thus an image-based measurement using camera system with fish eye lens offers an alternative means for accurate indirect measurement of LAI in oil palm. In this study, a methodology was developed to improve the leaf area index of the oil palm determination by hemispherical photography as an indirect method. A set of true LAI data, which collected by the direct method, was used as a reference to calibrate the LAI measurements obtained by hemispherical photography. The estimated LAI obtained by the hemispherical photographic method was underestimated as compared to the destructive method. Some means of calibration was necessary to determine the relationship between actual LAI and the hemispherical photographic LAI. The proposed correction factors will solve this underestimation effect. Protocol of the image analysis could minimize the error during image analysis. Developed LAI model can be used to estimate the accurate LAI by the hemispherical photographic method. The hemispherical photographic method seems a useful tool, which can confidently be used to estimate LAI of the oil palm. It can be used to estimate of the leaf area index (LAI) and as reliably as those obtained from the other indirect methods. This method could be popular due to its advantages, such as ease of use, the permanent photographs that can be use for other research purposes, comparatively cheaper and use of user-friendly image analysis software.